Tubuh, Pekerjaan, dan Pilihan Perempuan Jawa dalam Cengkraman Patriarki dan Kapitalisme - Syahr Banu (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2026)
Women’s bodies in Javanese society are often positioned not as personal property but as objects of social regulation legitimized by cultural norms. This study examines how patriarchy and capitalism operate simultaneously in shaping the bodies, work, and life choices of Javanese women, producing gender inequalities that are historical and structural in nature. This research employs a qualitative approach through historical and social analysis by examining historical sources and the contemporary social experiences of Javanese women. The findings show that women’s bodies function as political and economic arenas in which marriage norms, gender-based divisions of labor, and idealized body standards become key mechanisms of social control. These findings demonstrate that the inequalities experienced by Javanese women are not cultural givens but the result of historical processes continuously reproduced through cultural symbolism and capitalist logic. These processes restrict women’s autonomy in education, employment, and life decision-making within everyday social relations and layered power structures in contemporary Javanese society today. === Tubuh perempuan dalam masyarakat Jawa sering diposisikan bukan sebagai milik personal, melainkan sebagai objek regulasi sosial yang dilegitimasi oleh norma budaya. Penelitian ini mengkaji bagaimana patriarki dan kapitalisme bekerja secara simultan dalam membentuk tubuh, pekerjaan, dan pilihan hidup perempuan Jawa, sehingga menghasilkan ketimpangan gender yang bersifat historis dan struktural. Penelitian ini menggunakan pendekatan kualitatif melalui analisis historis dan sosial dengan menelaah sumber-sumber sejarah serta pengalaman sosial perempuan Jawa kontemporer. Hasil penelitian menunjukkan bahwa tubuh perempuan berfungsi sebagai arena politik dan ekonomi, di mana norma pernikahan, pembagian kerja berbasis gender, dan standar tubuh ideal menjadi mekanisme utama kontrol sosial. Temuan ini menunjukkan bahwa ketimpangan yang dialami perempuan Jawa bukanlah kodrat budaya, melainkan hasil dari proses historis yang terus direproduksi melalui simbolisme budaya dan logika kapitalisme. Proses tersebut membatasi otonomi perempuan dalam pendidikan, pekerjaan, serta pengambilan keputusan hidup dalam relasi sosial sehari-hari dalam masyarakat Jawa kontemporer modern.